Kebijakan Penanggulangan Kemiskinan Kota Semarang melalui Kartu Identitas Miskin - Ahmad Syarif Hardiansyah; Turtiantoro .; Wahid Abdulrahman (Journal of Politic and Government Studies, 2016)
Proverty is the main problem for developing countries. Every year, poverty is seriously highlighted since it causes hindrance for countries to advance. Today, not only rural areas have the problem, but urban areas or big cities as well. Semarang is not excluded. Based on data released by BAPPEDA Semarang, in the year 2015 the number of the poor in Semarang is 114.939 families or 367.848 individuals. This urges Semarang city government to issue a proverty reduction policy. One of the programs of the policy is collecting data of the poor and tagging them by giving Kartu Identitas Miskin, an identity card only for the poor. Kartu Identitas Miskin or KIM to identify the poor is used as reference for all proverty reduction programs in Semarang. Poverty reduction program in Semarang should base its execution to the collected data. This expects the program to reduce poverty is right on the target. The focus of this research is the implementation of the poverty reduction policies in Semarang city through KIM. The program execution is started with identify and verify the data of the poor every two years. This has been held in 2009 and continuing. The next step is executing the program which is planned based on the data. Satuan Kerja Perangkat Daerah (SKPD) is the executant. Author conducts research on the implementation process of poverty reduction programs done by Department of Health and Department of Education in Semarang as samples. Author finds that SKPD doesn’t fully refer to KIM beneficiaries in implementing the programs. Jaminan Kesehatan Masyarakat Kota, a health insurance for Semarang citizen provided by the government, can only be accessed with Surat Keterangan Tidak Mampu (SKTM), a certificate for people at economic disadvantage, even for people whom already have KIM. Lack of socialization process to the citizen makes a lot of information biases about the procedure and how to use KIM. Besides, author also finds that the enumeration of the data is not entirely valid and accurate. The officers doing enumeration still use their own subjectivity in registering the beneficiaries. Semarang government needs to do more efforts to improve KIM program, started with giving more control in identification and verification process. The validity of the collected data will lead the implementation right on the target. Keywords : proverty, Kartu Identitas Miskin, policy implementation